Influence of socioeconomic status on allograft and patient survival following kidney transplantation. (June 2015) - Ward, Frank L; O'Kelly, Patrick; Donohue, Fionnuala; ÓhAiseadha, Coilin; Haase, Trutz; Pratschke, Jonathan; deFreitas, Declan G; Johnson, Howard; Conlon, Peter J; O'Seaghdha, Conall M
Abstract: Aim: Whether socioeconomic status confers worse outcomes after kidney transplantation is unknown. Its influence on allograft and patient survival following kidney transplantation in Ireland was examined. Methods: A retrospective, observational cohort study of adult deceased‐donor first kidney transplant recipients from 1990 to 2009 was performed. Those with a valid Irish postal address were assigned a socioeconomic status score based on the Pobal Hasse‐Pratschke deprivation index and compared in quartiles. Cox proportional hazards models and Kaplan–Meier survival analysis were used to investigate any significant association of socioeconomic status with patient and allograft outcomes. Results: A total of 1944 eligible kidney transplant recipients were identified. The median follow‐up time was 8.2 years (interquartile range 4.4–13.3 years). Socioeconomic status was not associated with uncensored or death‐censored allograft survival (hazard ratio (HR) 1.0, 95% confidence interval (CI) 0.99–1.00, P = 0.33 and HR 1.0, 95% CI 0.99–1.00, P = 0.37, respectively). Patient survival was not associated with socioeconomic status quartile (HR 1.0, 95% CI 0.93–1.08, P = 0.88). There was no significant difference among quartiles for uncensored or death‐censored allograft survival at 5 and 10 years. Conclusion: There was no socioeconomic disparity in allograft or patient outcomes following kidney transplantation, which may be partly attributable to the Irish healthcare model. This may give further impetus to calls in other jurisdictions for universal healthcare and medication coverage for kidney transplant recipients. Summary at a Glance: Making use of postal address and census data (as a surrogate of socioeconomic status), data from an observational cohort of 1944 eligible adult kidney transplant recipients in Ireland suggested no disparity in allograft or patient survival.